A comparative study between Ash'arism and al Faruqi on selected theological issues - Abdul Rahim, Adibah (2013)
Ash'arism remains the orthodox sunni Islam for the present time. It has been influenced by many scholars including Ismail Raji al-Faruqi. This paper tries to present some of the theological ideas of al-Faruqi and compares them with Ash'arism. Few selected theological issues will be highlighted, such as, the relationship between reason and revelation, causality, and freewill or freedom of choice. Despite of understanding those issues from the perspective of classical Muslim theologians like al-Ash'ari, it is also important to highlight them in the light of modern approach of al-Faruqi which reflects them in more relevant values to our contemporary time. Al-Faruqi adopted different style of approaches in those issues. He brought the views of Ash'arism in a more complex approach in the modern age. Al-Faruqi has fulfilled one of the most urgent intellectual needs of the Muslim world as well as non-Muslim world. His contributions to non-Muslim world lie in his ability to make it appreciated Islam and its endowment to human civilization.